A newly bat-borne hantavirus detected in Seba's short-tailed bats (Carollia perspicillata) in the brazilian Atlantic Rainforest - Souza, Patrick Jesus de (2024)
Produção científica do Laboratório de Hantaviroses e Rickettsioses.